Dabigatran treatment simulation in patients undergoing maintenance haemodialysis - Liesenfeld, Karl-Heinz; Brückmann, Martina (Thrombosis and haemostasis, 2016)
Patients with atrial fibrillation requiring maintenance haemodialysis are at increased risk of ischaemic stroke and bleeds. Currently, vitamin K antagonists such as warfarin are predominantly used in these patients as limited data are available on the use of non-vitamin K oral anticoagulants, including dabigatran etexilate (dabigatran). Dabigatran is approximately 85 % renally eliminated, thus, its half-life is prolonged in renal impairment. This study simulated the dose-exposure relationship of dabigatran in patients undergoing haemodialysis. Dabigatran exposure was modelled at once- and twice-daily doses of 75 mg, 110 mg and 150 mg and at variations in non-renal clearance and dialysis settings. Resultant dose exposure (area under the curve [AUC]) was compared with values simulated from typical patients in the RE-LY ® trial (based on a previously characterised pharmacometric model). In this simulation, all twice-daily dosages resulted in exposures above those simulated from typical RE-LY patients (1.5- to 3.3-fold increase in AUC) and thus may not be optimal for use in haemodialysis patients. However, dabigatran doses of 75 mg or 110 mg once daily produced exposures comparable to those simulated in typical RE-LY patients (-13.3 and +4.4 %, respectively). Of patient and dialysis variables, non-renal clearance had the highest impact on exposure (≤30.8 % change). These data could potentially inform dose selection in patients undergoing maintenance haemodialysis and the findings warrant investigation in future clinical trials.